A mutation in the PSST homologue of complex I (NADH:ubiquinone oxidoreductase) from Tetranychus urticae is associated with resistance to METI acaricides. (January 2017) - Bajda, Sabina; Dermauw, Wannes; Panteleri, Rafaela; Sugimoto, Naoya; Douris, Vassilis; Tirry, Luc; Osakabe, Masahiro; Vontas, John; Van Leeuwen, Thomas
Abstract: The acaricidal compounds pyridaben, tebufenpyrad and fenpyroximate are frequently used in the control of phytophagous mites such as Tetranychus urticae, and are referred to as Mitochondrial Electron Transport Inhibitors, acting at the quinone binding pocket of complex I (METI-I acaricides). Because of their very frequent use, resistance evolved fast more than 20 years ago, and is currently wide-spread. Increased activity of P450 monooxygenases has been often associated with resistance, but target-site based resistance mechanisms were never reported. Here, we report the discovery of a mutation (H92R) in the PSST homologue of complex I in METI-I resistant T. urticae strains. The position of the mutation was studied using the high-resolution crystal structure of Thermus thermophilus, and was located in a stretch of amino acids previously photo-affinity labeled by fenpyroximate. Selection experiments with a strain segregating for the mutant allele, together with marker-assisted back-crossing of the mutation in a susceptible background, confirmed the involvement of the mutation in METI-I resistance. Additionally, an independent genetic mapping approach; QTL analysis identified the genomic region of pyridaben resistance, which included the PSST gene. Last, we used CRISPR-Cas9 genome editing tools to introduce the mutation in the Drosophila PSST homologue. Graphical abstract: Highlights: Target-site resistance of Tetranychus urticae to METI-I acaricides, inhibiting mitochondrial complex I, was investigated. A H92R substitution was identified in the PSST homologue of complex I from T. urticae in METI-I acaricide resistant strains. 3D-modeling revealed that H92R is located near the presumed binding site of ubiquinone and well-known complex I inhibitors. Genetic mapping and QTL analysis identified the genomic locus of pyridaben resistance, which included the PSST gene. Selection experiments and marker-assisted back-crossing showed that H92R is associated with METI-I resistance in T. urticae .